1982
DOI: 10.1530/jrf.0.0660031
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic development of the degu, Octodon degus

Abstract: Summary. Although the degu has a long gestation period (87 \ m=+-\ 3 days) the pattern of development from mating to birth is similar to that of other rodents. However, each of the basic processes occurs more slowly than in myomorph rodents and the degu could therefore be useful for studies on embryonic development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
2

Year Published

1984
1984
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 11 publications
0
21
0
2
Order By: Relevance
“…Paternal care and communal breeding characterize the desert-living striped mice Pillay 2003, 2004). In addition, we provide the first ossification-sequence data for the degu, Octodon degus, a small to medium-sized, diurnal, semi-fossorial and herbivorous caviomorph rodent common to the central region of Chile (Mess 2007;Rojas et al 1982). Studies of communal breeding in O. degus have shown that this rodent lives in groups with polygamous social structure (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Paternal care and communal breeding characterize the desert-living striped mice Pillay 2003, 2004). In addition, we provide the first ossification-sequence data for the degu, Octodon degus, a small to medium-sized, diurnal, semi-fossorial and herbivorous caviomorph rodent common to the central region of Chile (Mess 2007;Rojas et al 1982). Studies of communal breeding in O. degus have shown that this rodent lives in groups with polygamous social structure (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Octodon degus were maintained in the laboratory at 20-22°C under natural light and with free access to food and water. Foetuses were obtained according to the previously described method (Rojas et al 1982), as follows: females presenting a perforated vaginal membrane were joined with selected males; the initial day of pregnancy (day 0) was determined by the presence of spermatozoa in vaginal smears which were taken daily. Females were isolated and embryos obtained by laparatomy.…”
Section: Methodsmentioning
confidence: 99%
“…Octodontidae; Suborder Caviomorpha; Order Rodentia) has a longer period of gestation (range 87-93 days, see Weir 1974) than that of other rodents, and this permits an accurate study of the different phases of development. The embryonal development of this species has been analysed recently (Rojas et al 1982), and in 41-day post-coitum embryos a testis could be recognized.…”
mentioning
confidence: 99%
“…2011a). After a gestation period of 87 ± 3 days (Rojas, Montenegro & Morales ), females give birth to an average of 6 ± 1 precocial offspring (14 g, Long & Ebensperger ). The lactation period is relatively short, lasting ~30 days.…”
Section: Introductionmentioning
confidence: 99%
“…Sexual maturity occurs~6 months after birth (Mahoney et al 2011), with the primary mating season taking place during the late, austral fall (June) . After a gestation period of 87 AE 3 days (Rojas, Montenegro & Morales 1982), females give birth to an average of 6 AE 1 precocial offspring (14 g, Long & Ebensperger 2010). The lactation period is relatively short, lasting~30 days.…”
Section: Introductionmentioning
confidence: 99%